Novel low-cost assay for the monitoring of CD4 counts in HIV-infected individuals - Kriengkrai Srithanaviboonchai (2018)
Several CD4 lymphocyte enumeration methods have been developed to be used as alternatives to conventional flow cytometry. However, no consensus has been reached on which technique should be widely adopted. We introduce here a novel nonflow cytometric method, called CD4 Select, for enumeration of CD4 lymphocytes. Instead of using a flow cytometer, the method requires only an automatic hematoanalyzer (complete blood count [CBC] machine). The correlations of the percentage of CD4 lymphocytes and absolute CD4 counts with the CD4 Select method and standard flow cytometry were 0.932 and 0.922, respectively. The CD4 Select method yielded percentage of CD4 lymphocytes greater than flow cytometry by a mean of 0.06%, and the limits of agreement at 95% confidence interval (CI) were 9.46% to -9.56% using Bland-Altman analysis. The CD4 select method is cheap, valid, and simple enough to be conducted locally at small facilities. The method yields not only absolute CD4 lymphocytes, but also percentage of CD4 lymphocytes. The use of a hematoanalyzer also gives this method relatively high sample throughput and makes it less labor-intensive than other nonflow cytometric methods. © 2008 Lippincott Williams & Wilkins, Inc.